2010
DOI: 10.1103/physrevb.82.214109
|View full text |Cite
|
Sign up to set email alerts
|

Doping and temperature-dependent optical properties of oxygen-reducedBaTiO3δ

Abstract: We report on optical properties of reduced BaTiO 3−δ at different doping levels including insulating and metallic samples. In all the samples, including metallic one, we observe structural phase transitions from the changes of the infrared active phonon modes. Metallic ground state is confirmed by the Drude-type low-frequency optical reflectance. Similar to SrTiO 3−δ we find that the mid-infrared absorption band in BaTiO 3−δ appears and grows with an increase in the oxygen vacancy concentration. Upon decrease … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 64 publications
11
44
0
Order By: Relevance
“…The black data points in Figure 7 show how the force constant of the ferroelectric mode of BaTiO 3 evolves with electron doping. Consistent with previous studies, [121][122][123] even a small amount of doping (between 0.05 and 0.10 electrons/f.u.) suppresses the ferroelectric instability, i.e.…”
Section: Doping Dependence Of Polar Instabilitiessupporting
confidence: 92%
“…The black data points in Figure 7 show how the force constant of the ferroelectric mode of BaTiO 3 evolves with electron doping. Consistent with previous studies, [121][122][123] even a small amount of doping (between 0.05 and 0.10 electrons/f.u.) suppresses the ferroelectric instability, i.e.…”
Section: Doping Dependence Of Polar Instabilitiessupporting
confidence: 92%
“…While ferroelectric materials used in FTJs are normally considered as insulators, previous studies have found that ferroelectricity persists even in moderately electron-doped (i.e., metallic, or nearly so) BaTiO 3 [24,25]. These results were corroborated by theoretical studies showing that ferroelectric displacements in BaTiO 3 persist up to a doping level of about 0.1e per unit cell (∼10 21 =cm 3 ) [26,27].…”
supporting
confidence: 77%
“…For example, experiments have found that the ferroelectric phase persists deeply into the metallic phase of oxygen reduced BaTiO 3−δ . 27,28 Theoretical studies have demonstrated that ferroelectric displacements persist up to the doping level of about 0.1 e per unit cell (u.c.) in BaTiO 3 (BTO; ∼10 21 /cm 3 ) consistent with the experimental findings.…”
Section: Introductionmentioning
confidence: 99%